Training Second-Career Teachers: A Different Student Profile, A Different Training Approach? - Marlies Baeten; Wil Meeus (Educational Process: International Journal)
Second-career teachers are career changers who leave their current jobs to become teachers. This study conducts a narrative literature review which explores the student profiles of these teachers, asking how they differ from school leavers entering teacher education. The literature review also explores the characteristics of training approaches that are most suitable for second-career teachers based on their general student profile. Results show that second-career teachers are older, have strong intrinsic motivation, possess a wide range of knowledge and skills, have a self-directed and application-oriented approach to learning and teaching, and appreciate peer support. They benefit from teacher education programs that are flexible and include a preparatory period, that transfer their expertise into the teaching profession, provide opportunities for self-directed learning and peer support, integrate coursework and field experience, offer a significant amount of field experience and provide intensive mentoring support.